Pollinators as a tool for environmental education and awareness in an urban park (Biocenosis, 2024)
The loss of habitats due to deforestation, extensive agriculture, the use of agrochemicals, and urbanization threatens a large number of species around the world. A group that causes concern is the group of pollinators, as a high percentage of the food harvested worldwide directly depends on their intervention. The education and awareness of the general population, through the dissemination of precise and comprehensible scientific information, is key to promoting the protection of pollinators. For this, a scientific outreach strategy was designed, focused on four of the pollinator groups present in the country (bees, birds, butterflies, and bats) and the construction of four specialized pollinator gardens within La Libertad Metropolitan Park, located in the Desamparados canton, Costa Rica. The diversity of pollinator species was determined by conducting observations in the park during the months of September and October 2020. In 2021, a survey was conducted with visitors to assess their level of knowledge and interest in pollinator protection and the Park’s environmental efforts. Based on this data, a strategy was designed to elaborate four gardens, each specialized in a particular pollinator, complete with interpretive labeling.
Keywords: biophilia; conservation; environmental interpretation; pollination; interpretive labeling